ANALISIS BUTIR SOAL PILIHAN GANDA UJIAN AKHIR SEMESTER MAHASISWA DI UNIVERSITAS TERBUKA DENGAN PENDEKATAN TEORI TES KLASIK - Dewi Juliah Ratnaningsih; Isfarudi Isfarudi; Nuraini Soleiman (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2011)
Multiple choice tests have been used to measure students learning achievement for most of the courses at Universitas Terbuka (UT). To ensure the quality of the tests, test item analysis based on classical test theory has been employed regularly. This paper aims to analyze multiple-choice items of the End Semester Examination of UT using the program ITEMAN. The data used were the answers sheets of students taking eight courses in the first and second semester of 2009. Courses analyzed in this study were MKDU4111, PEMA4210, MKDU4109, ISIP4215, EKMA4214, ESPA4112, BIOL4110, and BIOL4119. The results showed that the test items used have had a pretty good quality. Average test item difficulties were fair. This was indicated by the mean value of P which ranged from 0.328 to 0.461. Discrimination index for both semester tests were good in about 75% of the courses measured. Its value ranges from 0.304 to 0.451 for the first semester of 2009 tests and 0.343 to 0.382 for the second semester of 2009 tests. Meanwhile, the reliability of the test items could be considered good except for the courses PEMA4210 (first semester 2009) and MKDU4111 (second semester 2009).